Genre Indicators in ChatGPT Chatbot Dialogue Steps - Marquardt, Dorota (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
This paper presents a typology and characteristics of frequently occurring types of dialogue steps in ChatGPT-3.5 chatbot conversations. Attention is paid to the design and structure, language and genre characteristics of such dialogue steps. Particular focus is placed on dialogical steps created by the chatbot without prompting with regard to style or specifying a particular genre in which a response is desired.